2021
DOI: 10.3390/microorganisms9122433
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes of Blood-Feeding Arthropods: Genes Coding for Essential Nutrients and Relation to Vector Fitness and Pathogenic Infections. A Review

Abstract: Background: Blood-feeding arthropods support a diverse array of symbiotic microbes, some of which facilitate host growth and development whereas others are detrimental to vector-borne pathogens. We found a common core constituency among the microbiota of 16 different arthropod blood-sucking disease vectors, including Bacillaceae, Rickettsiaceae, Anaplasmataceae, Sphingomonadaceae, Enterobacteriaceae, Pseudomonadaceae, Moraxellaceae and Staphylococcaceae. By comparing 21 genomes of common bacterial symbionts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 91 publications
(119 reference statements)
1
17
0
1
Order By: Relevance
“…Insect intestinal microbiota plays different roles such as gut cell proliferation, nutrient digestion and supplementation and toxin catabolism [38,[45][46][47][48]. Our results support the idea that this crosstalk between SLIMP and the commensal microbiota is capable to promote a very selective interference of the insect host in the microbial intestinal community, by the specific enrichment of the Bacteroidetes phylum (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Insect intestinal microbiota plays different roles such as gut cell proliferation, nutrient digestion and supplementation and toxin catabolism [38,[45][46][47][48]. Our results support the idea that this crosstalk between SLIMP and the commensal microbiota is capable to promote a very selective interference of the insect host in the microbial intestinal community, by the specific enrichment of the Bacteroidetes phylum (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…An earlier study by Zhang et al (2016) demonstrated that B. burgdorferi does not require thiamine or Vitamin B1, a key cofactor for most living organisms, for its growth and replication and that it may have evolved to live in a Vitamin B-constrained environment of the tick. Sonenshine and Stewart (2021) also raise the possibility that environmental bacteria that form the bulk of the ectosymbionts found in the midgut milieu are also capable of providing essential aminoacids, metabolites and vitamins to the tick and hence influence tick fitness and in-turn the vectorial capacity of the tick. Narasimhan et al (2014) have shown that changes in the environmental microbiota composition influence larval engorgement and B. burgdorferi colonization of the tick.…”
Section: Tick-b Burgdorferi-commensal Microbiota Interactionsmentioning
confidence: 99%
“…The at least 27 groups of peptide and protein salivary components of the Ixodidae comprise various members of the lipocalin, Kunitz domain, cystatin, basic tail, ixostatin, and metalloprotease families [42]. In addition, the composition can change significantly due to pathogen colonization [30,32,[43][44][45], and there even appears to be considerable interindividual variability among ticks of a single species, as demonstrated in Ixodes ricinus [46]. Ticks produce possibly the most complex saliva of all animals [47].…”
Section: Feeding and Salivary Secretionmentioning
confidence: 99%